A deliberação nos tribunais: a formação da decisão judicial por órgãos colegiados - André Garcia Leão Reis Valadares (2017)
The study of Brazilian procedures legislation, notably the constitutional and ordinary law reforms inaugurated in the 1990s and the new innovations brought by the 2015 Code of Civil Procedure, evidences the legislative efforts to reinforce the guidance established by the countrys Courts. In this regard, this study intends to discuss the structure in which trials are ruled by a panel of judges, especially the characteristics and purposes of organizing the courts in a collective body. In face of the aspects of the board of judges, the deliberative phenomenon, its philosophical base in the politics area and the compatibility within the Judiciary must be comprehended. Thus, this study aims to debate the elements that helps improve a Court deliberative performance in the three main phases of a judgment by collective body: pre-decisional phase, decisional phase, and post-decisional phase. After all, to insert deliberation as the element of collective ruling means to try to assign a model of rationality to such trial, for the purpose of legitimizing and improving the quality of judicial performance.